HAMBATAN-HAMBATAN HUKUM DALAM PENYELESAIAN TANAH GARAPAN PADA AREAL EKS HGU PTPN II KEBUN HELVETIA : ATAS ADANYA SK KBPN NOMOR 42/HGU/BPN/2002 - CHRISTINA CAROLYN (PREMISE LAW JURNAL, 2014)
ABSTRACT PT Perkebunan Nusantara II (PTPN II) is a state-owned enterprise which conducts a large part of its plantation business in North Sumatera. The status of the land rights controlled and managed by this company is regulated in the Land Law and Law No. 40/1966. The work on the land occurred during the Japanese occupation in Indonesia when there was an emergency in food supply so that people began to work on the estate land; since then, the work on land has become increasing. The result of the research showed that, according to SK KBPN No. 42/HGU/BPN/2002, dictums 3 and 4, it is stated that the management, the control, the ownership, and the use of land is handed over to the governor of North Sumatera and will be distributed to the appropriate persons before there is the discharge from the related Minister. Keywords: Legal Problems, the Settling of Crop Land, Area of Ex-Leasehold, PTPN II Helvetia Plantation.